Peningkatan Kemampuan Motorik Kasar Anak Melalui Permainan Engklek Di Raudlotul Athfal Hasyim Asyari Puger - Wiwik Fatmawati; Syamsi Rega Virgi Wulandari; Abdul Karim (PRESCHOOL: Jurnal Pendidikan Anak Usia Dini, 2022)
With the increase in gross motor skills through the crank locomotor movement in group A children in Raudlotul Athfal Hasyim Asyari Puger, it is expected to provide stimulation and experience an increase in students' gross motor skills. This research uses a qualitative approach and the type of research is descriptive. The technique of determining the research informants used purposive. Data collection techniques using observation, interviews, and documentation. Data analysis used a qualitative descriptive analysis of the Miles and Huberman model, which included data collection, data condensation, data presentation, and drawing conclusions. The validity of the data using triangulation of sources and techniques. Based on the results of the study, it was concluded: 1) Efforts to improve gross motor skills through the locomotor movement of the ankle at RA Hasyim Asyari Puger, namely: a) Train the crank ability slowly by resting on one leg, with the aim of training the knee muscles to be strong and agile and practicing dynamic balance children. b) Train the child's ability to run properly and agilely, for example, by running small without balance disorders. b) Practice the ability to jump accompanied by landing and good balance. 2) The implementation of learning the crank movement in improving gross motor skills at RA Hasyim Asyari Puger, namely: a) the teacher prepares the place, 2) the teacher prepares the material to be delivered, for example using raffia as a start and finish line, c) the teacher conditions the children into 2 group d) the teacher gives an example of the crank locomotor movement e) the teacher provides an evaluation of the students to measure the extent to which the locomotor movement learning goes as expected, such as balance, maintaining the body, and agility in moving.   Dengan adanya peningkatan kemampuan motorik kasar melalui gerak lokomotor engklek pada anak kelompok A di Raudlotul Athfal Hasyim Asyari Puger diharapkan memberikan rangsangan dan mengalami peningkatan dalam kemampuan motorik kasar peserta didik. Penelitian ini menggunakan pendekatan kualitatif dan jenis penelitian berbentuk deskriptif. Teknik penentuan informan penelitian menggunakan purposive. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data menggunakan analisis deskriptif kualitatif model Miles dan Huberman, yang meliputi pengumpulan data, Kondensasi data, penyajian data, dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi sumber dan teknik. Berdasarkan hasil penelitian disimpulkan: 1) Upaya meningkatkan kemampuan motorik kasar melalui gerak lokomotor engklek di RA Hasyim Asyari Puger, yaitu: a) Melatih kemampuan engklek secara pelan dengan bertumpu pada satu kakinya, dengan tujuan melatih otot lutut agar kuat dan lincah serta melatih keseimbangan dinamik anak anak. b) Melatih kemampuan berlari anak dengan tepat dan lincah misalnya engklek dengan berlari kecil tanpa gangguan keseimbangan. b) Melatih kemampuan melompat dengan disertai pendaratan dan keseimbangan yang baik. 2) Pelaksanaan pembelajaran gerakan engklek dalam meningkatkan kemampuan motorik kasar di RA Hasyim Asyari Puger, yaitu: a) guru menyiapkan tempat, 2) guru menyiapkan bahan yang akan disampaikan misalnya menggunakan tali rafia sebagai garis start dan finish, c) guru mengkondisikan anak menjadi 2 kelompok d) guru memberikan contoh gerakan lokomotor engklek e) guru memberikan evaluasi terhadap anak didik untuk mengukur sejauh mana pembelajaran gerak lokomotor tersebut berjalan sesuai harapan, seperti keseimbangan mempertahankan tubuh, dan kelincahan dalam bergerak